PENGGUNAAN VLOG DALAM PEMBELAJARAN MAHĀRAH KALĀM - Mubarak, Mahfuz Rizqi; Wahdah, Nurul; Ilmiani, Aulia Mustika; Hamidah, Hamidah (STIQ Amuntai, 2020)
This study aims to explore the use of vlog in learning Mahārah kalām. The formulation of the problem in this study is: how to use Vlogs in learning Mahārah kalām and What is the perception of students regarding the use of Vlogs on learning Mahārah kalām. This study uses descriptive qualitative research methods with trianguliation techniques namely observation, interviews, and documentation. The results revealed the use of Vlog /Vlogging in Mahārah kalām learning using the following steps: (1) Determination of the theme by lecturers supporting the course, (2) Preparation of ideas as material for making scripts/scenarios, (3) Site selection, (4) Evaluation of results, (5) and publication of Vlog video results on social media accounts. received a very positive response from students of the IAIN Palangka Raya Language Education Study Program. 28 out of 30 students gave positive responses regarding the use of Vlogs in the learning of Mahārah kalām. This positive response is based on several reasons: its use is easy, flexible, practical, and economical. Students are also required to be more creative in making vlogging videos so as to produce a good video. but the use of Vlog is also not free from negative responses such as cheating by students who seem to hide the text/script behind the camera so that the video presented is not entirely pure from the results of Mahārah kalām.